Challenges in the automated synthesis of [18F]-1-fluoroethyl tryptophan: Formation of both O- and N-alkylated products. (January 2018) - Venkatachalam, T.K.; Stimson, D.H.R.; Pierens, G.K.; Bhalla, R.; Reutens, D.C.
Abstract: [ 18 F]Fluoroethyl tosylate was synthesized using an automated "Synthra" module using ethylene di-tosylate and [ 18 F]fluoride/K222 /K2 CO3 in acetonitrile. [ 18 F]Fluoroethyl tosylate was purified by semi-preparative HPLC followed by reformulation using a C18 Sep-Pak cartridge and eluted with DMF. Using this [ 18 F]fluoroethyl tosylate, we attempted to alkylate protected tryptophan aiming to obtain the N-[ 18 F]fluoroethyl-t-Boc-tryptophan methyl ester. Initial attempts resulted in the formation of the O-alkylated, rather than N-alkylated product. Manual removal of the cartridge from the automated module, followed by an extended drying of the cartridge under high flow nitrogen, was required to form the desired N-alkylated product. This demonstrates that the drying process in automated modules requires modification for sensitive N-alkylation of compounds and may be essential for compounds like tryptophan methyl ester that have multiple potential sites of alkylation in their chemical structure. Highlights: Synthesis of 1-N-alkylated tryptophan. Radiolabeling. Drying of 18 F-ethyl tosylate. N and O alkylations.